Influência de fatores históricos e da fragmentação do habitat sobre a diversidade genética de Pseudoplatystoma corruscans (Siluriformes: Pimelodidae) - Silva, Alline Braga (Universidade Federal de São Carlos, 2015)
The populations of Neotropical inland fishes have the distribution of their genetic diversity influenced by historical and recent biogeographic factors. Natural barriers such as the formation of waterfalls can disrupt gene flow between populations upstream and downstream. In addition, river fragmentation by hydroelectric dams also impacts on gene connectivity and, moreover, it exposes population to more intense evolutionary forces, such as genetic drift. The effects of habitat fragmentation are more pronounced in migratory species, which move large distances to reproduce. Among these species, Pseudoplatystoma corruscans, a piscivorous catfish, plays an important ecological role as top predator. In addition, this fish represents the main income for thousands of riverine families. Understanding the influence of historical factors on the population structuring is important for species conservation, because it helps in decision making, such as the determination of management units and guidelines for conducting restocking. On the other hand, analysis of recent factors such as river fragmentation can indicate the impact of habitat fragmentation on the population viability, since smaller populations show greater effects of genetic drift and inbreeding. Having said that, we have analyzed the influence of historical and recent events on the genetic diversity distribution of P. corruscans. For historical events, we collected samples of P. corruscans in all basins of its natural occurrence (São Francisco, Paraná, Paraguay and Uruguay) and used markers with slow mutational rates (S7-íntron1, CITB and D-loop). For recent events, we used microsatellite markers, with high mutational rates. We collected samples in four sections of different sizes of rivers bordered by dams (Grande, Verde, Paraná and Paraguay). The mitochondrial markers indicated the existence of two groups, one in the São Francisco basin and another in the Prata basin (Paraná, Paraguay and Uruguay). The three genes analyzed showed private haplotypes for populations in the São Francisco basin, although S7-íntron1 marker has indicated the existence of only one clade for all basins. These results indicate that the geographical separation between San Francisco and Upper Paraná promoted genetic differentiation between populations of the two basins. On the other hand, the “Sete Quedas” fall, which historically separated the Upper Paraná and Paraguay basins, was not enough to promote population structuring. Probably the two basins were connected by headwaters. Thus, we suggest that conservation efforts are earmarked for two large basins (São Francisco and Prata), with a special look to Prata basin, since the species is threatened with extinction in the Uruguay basin, addition to the large number dams present in the Paraná basin. Regarding the river fragmentation caused by dams, smaller river stretches had lower genetic diversity and greater kinship between their individuals, which can result in lower population viability, since there is an increase of inbreeding depression and loss of adaptive genetic diversity. We therefore suggest that studies with other species are performed to determine the stretch minimum size in which the populations of migratory fish are viable, providing guidelines for the construction of new dams.
Keywords: Peixes neotropicais migradores; Eventos biogeográficos; Impactos de usinas hidrelétricas; Neotropical migratory fishes; Biogeographic events; Impacts of hydroelectric plants; CIENCIAS BIOLOGICAS